Greek Island Temple Complex Reveals ‘Countless’ Offerings Left by Ancient Worshippers - Associated Press (Les Carnets de l’ACoSt)
As appeared in the AP News: Archaeologists excavating a hilltop sanctuary on the Aegean Sea island of Kythnos have discovered “countless” pottery offerings left by ancient worshippers over the centuries, Greece’s Culture Ministry said Wednesday.A ministry statement said the finds from work this year included more than 2,000 intact or almost complete clay figurines, mostly of women and children but also some of male actors, as well as of tortoises, lions, pigs and birds.